3+8n=6n-1

Simple and best practice solution for 3+8n=6n-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+8n=6n-1 equation:


3+8n=6n-1

We simplify the equation to the form, which is simple to understand
3+8n=6n-1

We move all terms containing n to the left and all other terms to the right.
+8n-6n=-1-3

We simplify left and right side of the equation.
+2n=-4

We divide both sides of the equation by 2 to get n.
n=-2

See similar equations:

| 3(3y-9)=2(y-3) | | (90-x)=1/5(180-x)-10 | | 5ab+3a^2b-0.5ab= | | 50=-2(24-x)+4(x-4) | | -3n+1=-4n+8 | | 9=3y-5x | | a^2-9a+7a-63=0 | | 13602.48=2*3.14r^2+2*3.14*r*95 | | 6=X-4 | | 4(2s-3)=(s+1) | | 4k+6=16+6k | | 14b+3c= | | 7x+3=3-13 | | -1.6x=9.2 | | y(y-9)= | | 3(2*3.5-1)=9(2*3.5-5) | | 33=4n-7+6n | | 9(4y^2+2y+3)= | | 0.3(t-3)=0.4t | | 5(6x+6)=60 | | 2(n+5)+3n=-20 | | 10t-15=85 | | 5m-29=-8m-3 | | 11=y-12 | | 27.5+42.5= | | x+4y+3=0 | | 5(x+1)-2(2x-4)= | | 15y-45+135b= | | -1-6v=-5v+2 | | (7-2z)z= | | -6x+1-8x^2=-7x^2 | | x^2+6x=1015 |

Equations solver categories